Tax Avoidance as a Sustainability Problem - Bird, Robert (Journal of business ethics, 2018)
This manuscript proposes that tax avoidance can be better understood and mitigated as a sustainability problem. Tax avoidance is not just a financial problem for tax authorities, but one that erodes critical common spaces necessary for the smooth functioning of regulatory compliance, organizational integrity, and society. Defining tax avoidance as a sustainability problem offers a broader and more holistic understanding of the organizational and societal consequences of tax avoidance behavior. Sustainability is also a mature and legitimized concept that can readily incorporate taxation. A variety of established sustainability metrics have the capacity to incorporate anti-tax avoidance measures or publicize firms that engage in fair tax practices. This manuscript concludes that integrating sustainability principles, in conjunction with important extant work on corporate social responsibility and taxation, can advance the goals of decreasing the occurrence and acceptability of tax avoidance.